2022
DOI: 10.1007/s10126-022-10093-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Analyses Provide Insights into the Growth and Development Advantages of Triploid Apostichopus japonicus

Abstract: Polyploid breeding is widely used in aquaculture as an important area of new research. We have previously grown Apostichopus japonicus triploids with a growth advantage. The body length, body weight, and aestivation time of triploid and diploid A. japonicus were measured in this study, and the transcriptome and metabolome were used to examine the growth advantage of triploids A. japonicus. The results showed that the proportion of triploid A. japonicus with a body length of 6–12 cm and 12–18 cm was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Because sea cucumbers show the remarkable ability of quickly replacing injured organs, transcriptomes have been generated on H. glaberrima, E. fraudatrix , and A. japonic us during gut evisceration and regeneration [ 44 , 115 , 123 , 124 , 136 , 144 , 145 ], radial organ complex regeneration [ 109 ], and muscle regeneration [ 111 ]. Other studies explored gene expression during aestivation, a process that so far has been exclusively observed in sea sponges and sea cucumbers [ 159 , 174 176 ]. Moreover, transcriptomes exploring the response of the immune system have been generated in different conditions, such as air exposure stress [ 150 ], continuous heat stress [ 162 ], skin ulceration [ 167 ], microplastic [ 105 ] and nanoplastic toxicity [ 177 ], miRNA regulation in coelomocytes during host–pathogen interaction [ 179 ] and lipopolysaccharide treatment [ 109 ], knock-down of ajpacifastin-like gene [ 93 ], and exposure to Vibrio splendidus [ 130 ].…”
Section: Genomic-transcriptomic Information and Cellular And Molecula...mentioning
confidence: 99%
“…Because sea cucumbers show the remarkable ability of quickly replacing injured organs, transcriptomes have been generated on H. glaberrima, E. fraudatrix , and A. japonic us during gut evisceration and regeneration [ 44 , 115 , 123 , 124 , 136 , 144 , 145 ], radial organ complex regeneration [ 109 ], and muscle regeneration [ 111 ]. Other studies explored gene expression during aestivation, a process that so far has been exclusively observed in sea sponges and sea cucumbers [ 159 , 174 176 ]. Moreover, transcriptomes exploring the response of the immune system have been generated in different conditions, such as air exposure stress [ 150 ], continuous heat stress [ 162 ], skin ulceration [ 167 ], microplastic [ 105 ] and nanoplastic toxicity [ 177 ], miRNA regulation in coelomocytes during host–pathogen interaction [ 179 ] and lipopolysaccharide treatment [ 109 ], knock-down of ajpacifastin-like gene [ 93 ], and exposure to Vibrio splendidus [ 130 ].…”
Section: Genomic-transcriptomic Information and Cellular And Molecula...mentioning
confidence: 99%
“…Interestingly, in eastern oysters, Zeng and Guo (2022) identified a set of genes that are both important for biomineralization and growth. With triploid sea cucumber Apostichopus japonicus , the term ribosome production was enriched in fast growing sea cucumbers, and a set of 11 significant differential metabolites were found to be associated with growth advantage ( Xie et al, 2022 ).…”
Section: Review Of Recent Progress Of Genetic and Epigenetic Studies ...mentioning
confidence: 99%
“…Liver transcriptome analysis not only identified that genes were involved in the responses of turbot to different salinity conditions, but also demonstrated that low salinity exposure disorders turbot lipid metabolism ( Liu et al, 2020 ). Transcriptomic and metabolomic analyses indicated that when compared with diploid Apostichopus japonicus , triploid A. japonicus had more advantages in immunity, growth and development, stress resistance and adaptability to a harsh living environment ( Xie et al, 2022 ). Based on RNA-seq, comparative transcriptome analysis of different tissues in Lota dalliance provided a reference for enriching gene resource ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%